English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

i worked the problem out, but i'm unsure if it is correct--
3x + y = 4
x + 2y = 3

does x= 2.2? and y= - 2.6??

tell me if i did anything wrong.

-thanks [:

2007-09-18 10:38:18 · 21 answers · asked by gratisfaction. 5 in Science & Mathematics Mathematics

21 answers

Well...

3x + y = 4
x + 2y = 3

y = 4 - 3x
x + 2*(4 - 3x)=3

-5x = -5 ---> x = 1

y=4-1*3=4-3=1

The answer is: x=1; y=1

I don't know where you are wrong...this is the correct method.

2007-09-18 10:41:43 · answer #1 · answered by Anonymous · 0 2

Substitution Method

3x + y = 4- - - - - Equation 1
x + 2y = 3- - - - --Equation 2
- - - - - - - -

Isolate y in equation 1

3x + y = 4

Transpose 3x

3x + y - 3x = - 3x + 4

y = - 3x + 4

Substitute the y value into equation 2

- - - - - - - - -

x + 2y = 3

x + 2(- 3x + 4) = 3

The distributive property on the right side of the equation.

x + ( - 6x + 8 ) = 3

Remove parenthesis

x - 6x + 8 = 3

Collect like terms

- 5x + 8 = 3

Transpose 8

- 5x + 8 - 8 = 3 - 8

Collect like terms

- 5x = - 5

Divide both sides of the equation by - 5

- 5x / - 5 = - 5 / - 5

x = - 5 / - 5

x = 1

Insert the x value into eqjation 1
- - - - - - - -

3x + y = 4

3(1) + y = 4

3 + y = 4

Transpose 3

3 + y - 3 = 4 - 3

Collect like terms

y = 1

Insert the y value into equation 1
- - - - - - - - -

Check for equation 1

3x + y = 4

3(1) + 1 = 4

3 + 1 = 4

4 = 4
- - - - - - - -

Check for equation 2

x + 2y = 3

1 + 2(1) = 3

1 + 2 = 3

3 = 3
- - - - - - - - -

Botjh equations balance

The solution set is { 1, 1 }

- - - - - - - -s-

2007-09-18 10:58:34 · answer #2 · answered by SAMUEL D 7 · 0 0

no but x=1 then y=1

2007-09-18 10:46:25 · answer #3 · answered by mramahmedmram 3 · 0 0

The answer on both is 1, if you go, 3x+y=4, then 3+1 = 4.
x+2y=3, 1 +2y= 3., 1+ 2 = 3.
Second one both x and y are 1.

2007-09-18 10:43:45 · answer #4 · answered by Dragon'sFire 6 · 0 0

3x + y = 4

y = 4 - 3x

replacing y by (4-3x) in x + 2y = 3

x + 2 (4-3x) = 3

x+8-6x = 3

-5x = -5
5x = 5
x = 1

replacing x with 1 in y = 4 - 3x
y = 4 - 3(1)
y = 1

s0, x=1 and y=1

Verification:

3x + y = 4
3(1) + 1 = 4
4 = 4

x + 2y = 3
1+2(1) = 3
3 = 3

2007-09-18 11:19:50 · answer #5 · answered by sanju 5 · 0 0

To answer a question like this, you need to solve for x or y in one of the equations and then plug that number into the other equation.

For example. 3x + y = 4 so y = 4 - 3x

Now you take the 4-3x and plug it into the second equation in place of the y. Like this:

x + 2 (4 - 3x) = 3 now you have only one variable in your equation (the y is gone) and can solve for x

x + 8 - 6x = 3, so x - 6x = 3 - 8, so -5x = -5, so x = 1

now that you know that x = 1, plug it into either of the original equations to compute y

3(1) + y = 4, so y = 4 - 3, so y = 1

2007-09-18 10:53:05 · answer #6 · answered by Jesse 2 · 0 0

y= 1 and x= 1

you should use elimination..
3x + y = 4
x + 2y = 3

x + 2y = 3 turns into 3x + 6y = 9
because you need to multiply the equation by 3.
why? because in order to eliminate one of the variables (x, y, etc.) you need either the x's or the y's in both equations to be the same.

so now your new equations are
3x + 6y = 9
3x + y = 4

subtract these two equations to cancel out x.
3x + 6y = 9
- 3x + y = 4
------------------
5y=5
so y= 1

and then go back to substitute y as 1 in either of the two equations to get x.

take the equation 3x + 6y = 9.
substitute y as 1.
so the new equation would be 3x + 6(1) =9.
solve it to get 3x=3, or x=1.

therefore, the answer is y=1 and x=1 (:

2007-09-18 10:48:23 · answer #7 · answered by demarestian 1 · 0 0

3x+y=4
x+2y=3
u multiply 2(3x+y=4) = 6x+2y=8
1( x+y=3) = x+2y=3u subtract each value by corresponding one eg x to x & y to y
5x=5 divide both by 5
x=1.
to get y u substitute x by its real value,1.u pick either of the equations. (3times x)3+y=4, y=4-3, y=1
so x=1 while y=1.

2007-09-18 10:51:48 · answer #8 · answered by Swit .b 1 · 0 0

Solve one equation for y

y = 4 - 3x

Substitute it in for the other y

x + 2(4 - 3x) = 3

Solve for x

x + 8 - 6x = 3
- 5x = -5
x = 1

Now solve for y

x + 2y = 3
(1) + 2y = 3
2y = 2
y = 1

While your solution works for the 1st equation, it does not solve the 2nd.

2007-09-18 10:50:28 · answer #9 · answered by saberhilt 4 · 0 0

y = 4-3x
so x +2(4-3x)= 3
x+8-6x=3
-5x = -5
x= 1
1 +2y=3
2y =2
y=1

2007-09-18 10:48:56 · answer #10 · answered by ironduke8159 7 · 0 0

fedest.com, questions and answers